MEASURES OF SUPPORT TO THE DEVELOPMENT OF AGRICULTURAL COOPERATIVES IN THE REPUBLIC OF SERBIA - Đurić, Katarina (Ekonomija - teorija i praksa, 2022)
Cooperatives are an organizational form of association that has an extremely long tradition, and at the same time it is widespread in all parts of the world and in a large number of economic and non-economic activities. One of the areas in which cooperatives are most represented is agriculture. Association in the agricultural sector brings a number of benefits to farmers, and is one of the factors that contributes to the sustainable development of rural areas. The practice of most developed countries is to support cooperatives, primarily through agricultural policy measures. The aim of the research is to analyze the current situation and limitations on the further development of the cooperative sector. Also, by analyzing current measures, primarily financial support to cooperatives, the authors try to determine the extent to which the existing support mechanisms are adapted to the needs of cooperatives and in what ways could the positive impact of support measures be increased. The existence of financial support to the existing and newly formed cooperatives in the field of agriculture, agritourism and crafts in rural areas, which is achieved in the form of various development programs, is assessed as a positive step compared to the previous practice in which the cooperative sector was largely marginalized. Following the experiences of countries with developed agricultural cooperatives, the authors point out that only through consistent support measures and coordinated work of all entities in the agricultural sector can we expect the reaffirmation of the concept of cooperatives in agricultural practice.